Analisis Awal tentang Prasyarat Munculnya Gerakan Ta'dibiy dalam Kerangka Pemikiran al-Attas - Sharifah Hajar Syed Ahmad; Tatiana Denisova (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2026)
Past and contemporary Islamic movements overwhelmingly focused on political and economic reform, often neglecting the inner moral and intellectual condition of the individual. This paper argues that such neglect results from a fundamental confusion about the nature of education itself. The paper critiques the corporatisation of education and the reduction of authority to institutional structures rather than personal moral-intellectual integrity. The analysis offers a philosophical groundwork for rethinking Islamic educational initiatives beyond neoliberal and activist frameworks. Drawing principally on the educational philosophy of Syed Muhammad Naquib al-Attas, the paper inspired by his concepts of adab (recognition and acknowledgement of proper order) and ta'dib (the inculcation of that order) as the necessary foundations for any authentic reforming initiative without neglecting education as its core; this process is what we name it the islamic educational movement.. We propose that such a movement must fulfil two preconditions. First, it must recognise the type of order it seeks, distinguishing between temporal orders (economic, political) which are sustained by external maintenance, and eternal orders (knowledge, truth) sustained by conscious commitment and integrity. Second, it must preserve the integrity of knowledge through the moral-spiritual refinement of the knower, as well as courageous actions that acknowledge its rightful places within the hierarchy of that type of order. It concludes that without recovering adab in the individual self discipline of their soul, no collective reform, however well organised, can restore justice (‘adl) or truth.